Leaping lizards landing on leaves: escape-induced jumps in the rainforest canopy challenge the adhesive limits of geckos. Issue 131 (30th June 2017) - Higham, Timothy E.; Russell, Anthony P.; Niklas, Karl J.
Abstract : The remarkable adhesive capabilities of geckos have garnered attention from scientists and the public for centuries. Geckos are known to have an adhesive load-bearing capacity far in excess (by 100-fold or more) of that required to support their body mass or accommodate the loading imparted during maximal locomotor acceleration. Few studies, however, have investigated the ecological contexts in which geckos use their adhesive system and how this may influence its properties. Here we develop a modelling framework to assess whether their prodigious adhesive capacity ever comes under selective challenge. Our investigation is based upon observations of escape-induced aerial descents of canopy-dwelling arboreal geckos that are rapidly arrested by clinging to leaf surfaces in mid-fall. We integrate ecological observations, adhesive force measurements, and body size and shape measurements of museum specimens to conduct simulations. Using predicted bending mechanics of petioles and leaf midribs, we find that the drag coefficient of the gecko, the size of the gecko and the size of the leaf determine impact forces. Regardless of the landing surface, safety factors for geckos range from a maximum of just over 10 to a minimum of well under one, which would be the point at which the adhesive system fails. In contrast to previous research that intimates that gecko frictional adhesive capacity is excessive relative to body mass, we demonstrate that realistic conditions in nature may result in frictional capacity being pushed to its limit. The rapid arrest of the lizard from its falling velocity likely results in the maximal loading to which the adhesive system is exposed during normal activities. We suggest that such activities might be primary determinants in driving their high frictional adhesive capacity.